Side Effects of Technological Practices on 21st-century Skills of Gifted Students - María Isabel Gómez-León (International Journal of Sociology of Education)
Part of the research has focused on developing new technologies that contribute to fostering 21st-century skills in gifted students. However, some authors warn that the improper use of these technologies may lead to generations of passive users rather than critical thinkers, creators, and problem solvers for society. The objective of this study is to analyze the side effects of technological practices on the development of 21st-century skills in gifted students. To this end, a systematic review of articles published between 2010 and 2025 was conducted, following the PRISMA declaration guidelines. The final selection consisted of 40 articles, whose risk of bias was assessed using the Cochrane RoB 2 tool for randomized controlled trials and the ROBINS-I tool for non-randomized studies. Findings indicate that, although the use of new technologies has enormous potential for developing 21st-century skills in gifted students, the current education system may be fostering a lack of motivation for deep learning and creative production, ultimately leading to the misuse of these tools.